Advances in asthma: the role of exhaled nitric oxide in the assessment and management of asthma - Taylor, Robin (Henry Stewart Talks, 2011)
Exhaled nitric oxide (NO) in asthma, The relationship between exhaled NO and airway inflammation, Use of exhaled NO in diagnosis of respiratory symptoms, Exhaled NO as a predictor of steroid responsiveness, Strengths and weaknesses use of exhaled NO in monitoring asthma, Guideline for the clinical application of exhaled NO